Design of a Smoker-Dryer for Chicken - Guidzavai, Alphonse Sawalda; Ndjiya, Ngasop; Tchami, Hilaire; Njintang, Nicolas (European Scientific Journal, ESJ, 2024)
Chicken breeders, particularly those in Ngaoundéré-Cameroon, after 45 days of breeding find themselves confronted with the problems of wasting nutrients and resources. In most cases, they sell their chicken at low prices to avoid expenses. Faced with these problems, a few of them use various methods to preserve their chicken after 45 days of breeding, including cold preservation, smoking and drying. Cold preservation is the most widely used technique, but this technique is energy-intensive, without forgetting the untimely power cuts, and the deterioration of the quality of the product. By getting closer to its stakeholders, we were able to identify their difficulties, why they use cold preservation more and they also entrusted us with the characteristics of equipment that could meet their requirements. In this article we presented the results from functional analysis to 3D modeling through the search for solutions to resolve contradictions. It emerges from this study that the designed model guarantees food safety, user safety, retains all nutrients, ergonomic, uses fewer resources, fast, adaptable to any type and size of smoking products and that it is possible to achieve it industrially.